High burdens of phosphorylated tau protein and distinct precuneus atrophy in sporadic early-onset Alzheimer’s disease - Xinyi Lv; Zhaozhao Cheng; Qiong Wang; Feng Gao; Linbin Dai; Chen Du; Chang Liu; Qiang Xie; Yong Shen; Jiong Shi (Science Bulletin, 2023)

Phytoplankton community response to episodic wet and dry aerosol deposition in the subtropical North Atlantic - Zhongwei Yuan; Eric P. Achterberg; Anja Engel; Zuozhu Wen; Linbin Zhou; Xunchi Zhu; Minhan Dai; Thomas J. Browning (Limnology and Oceanography, 2023)
Atmospheric aerosol deposition into the low latitude oligotrophic ocean is an important source of new nutrients for primary production. However, the resultant phytoplankton responses to aerosol deposition events, both in magnitude and changes in community composition, are poorly constrained. Here, we investigated this with 19 d of field and satellite observations for a site in the subtropical North Atlantic. During the observation period, surface dissolved aluminum concentrations alongside satellite‐derived aerosol and precipitation data demonstrated the occurrence of both a dry deposition event associated with a dust storm and a wet deposition event associated with strong rainfall. The dry deposition event did not lead to any observable phytoplankton response, whereas the wet deposition event led to an approximate doubling of chlorophyll a , with Prochlorococcus becoming more dominant at the expense of Synechococcus . Bioassay experiments showed that phytoplankton were nitrogen limited, suggesting that the wet deposition event likely provided substantial aerosol‐derived nitrogen, thereby alleviating the prevalent nutrient limitation and leading to the rapid observed phytoplankton response. These findings highlight the important role of wet deposition in driving rapid responses in both ocean productivity and phytoplankton community composition.

Blood-based biomarkers for Alzheimer’s disease: a multicenter-based cross-sectional and longitudinal study in China - Feng Gao; Linbin Dai; Qiong Wang; Chang Liu; Kexue Deng; Zhaozhao Cheng; Xinyi Lv; Yan Wu; Ziyi Zhang; Qingqing Tao; Jing Yuan; Shiping Li; et al. (Science Bulletin, 2023)

Exploring the global trade networks of the tungsten supply chain: Insights into the physical and monetary mismatch among countries - Linbin Tang; Peng Wang; Zijie Ma; Stefan Pauliuk; Wei‐Qiang Chen; Tao Dai; Zipeng Lin (Journal of Industrial Ecology, 2023)
International trade is essential to bridge the imbalance between supply and demand of materials along with different nations effectively, especially for critical raw materials such as tungsten that are highly geographically unequally distributed. However, the international trade flows and their complex networks that link those participating nations have remained largely unexplored, which leads to inexplicable concerns for materials' criticality and their supply risks. By integrating the material flow analysis and the complex network analysis, this study traces the global trade flows of tungsten in various forms ranging from primary products to scrap among 223 countries and regions annually from 2000 to 2018 and explores the evolution of participating countries' role involved in international trade networks from both physical and monetary perspectives. We found that (1) there are ∼2673 thousand metric tons of tungsten feeding into supply chains globally during the 19 years, and about 96% of tungsten resources are re‐allocated from Asia to the high‐income regions; (2) the high‐income countries gain the potential benefits from both the resources and economic perspectives and they import 72% of tungsten resources in the form of primary and semi‐products from developing countries, meanwhile earning 87% of global tungsten trade value by exporting tungsten metal products with high value‐added back to those tungsten resources suppliers. Under the growing national interconnections of global tungsten trade networks, this study urges more cooperative actions and targeted supply chain management among the participating countries to secure the tungsten supply and sustainability of the global tungsten cycle.

Mapping China's copper cycle from 1950–2015: Role of international trade and secondary resources - Min Hao; Linbin Tang; Peng Wang; Heming Wang; Qiao-Chu Wang; Tao Dai; Wei-Qiang Chen (Resources, Conservation and Recycling, 2023)